Experimental investigation on thermal performance of polyurethane foam mattresses with PCM - M. Raja; S. Sivalakshmi; T. Balusamy; B. Musthafa; M. Sudharshan; Ashish Goyal; Abhijit Bhowmik (Discover Applied Sciences)
Abstract This study aims to analyse the heat dissipation characteristics polyurethane foam mattresses by integrating Phase Change Materials (PCMs). such as Low-Density Foam, High Density Foam, Low Density Foam with PCM, High Density Foam with PCM, Ventilated Low Density Foam, Ventilated High Density Foam, Ventilated Low Density Foam with PCM, and Ventilated High-Density Foam with PCM were meticulously studied in a controlled environment. By systematically varying foam density, PCM inclusion, and airflow optimization strategies, this research identifies the most effective configuration for achieving superior thermal comfort and temperature regulation. It is observed form the studies that the low-density polyurethane foam mattress integrated with PCM demonstrates promising thermo-regulatory performance, making it a viable option for individuals seeking enhanced sleep quality.